When the Translator Does More than Translate: A Case Study of Translator Roles in a Digital Publishing Initiative - Marin-Lacarta, Maialen; Vargas-Urpi, Mireia (HERMES - Journal of Language and Communication in Business, 2018)
Recent technological changes have affected translators’ professional boundaries and status. However, scant attention has been paid to the new opportunities that have been created for professional literary translators. Our research focuses on ¡Hjckrrh!, a de facto non-profit self-publishing initiative led by three professional translators who are involved in the publishing of literary translations in ebook format – they share the same professional expertise, but assume different roles in the initiative. An ethnography-inspired qualitative method has been adopted by the researchers. This paper is based on fourteen interviews with participants who have collaborated with ¡Hjckrrh!, comprising eleven translators (including the three founding members of ¡Hjckrrh!), two proofreaders and a graphic designer. The paper aims at studying translators’ roles, production teams and relationships, and pays special attention to the agency and visibility of translators. Our findings show that technology has had a positive impact on translator agency, status and identity among the founding members and collaborators of ¡Hjckrrh!. These translators have used the shifting professional boundaries and technological advances to develop their roles as cultural mediators. The article describes the work of the translators who collaborate in this digital initiative and discusses the ways they relate to each other, the roles they play and how they cross professional boundaries. The conclusions identify the relationships and opportunities created by this new work environment.